ARTGEO: ensino interdisciplinar - Benutti, Maria Antonia [UNESP]; Neves, Aniceh Farah [UNESP]; Nascimento, Roberto Alcarria do [UNESP]; Gonçalves, Solange Maria Leão [UNESP] (My University, 2010)
The ARTGEO Project aimed at integrating science, art, and technology, emphasizing geometric elements which must be explored within the teaching process. Geometry, present in the most primitive civilizations, assists man in settling relationships and organizing his space. It has been clearly identified in human constructions, consisting of an important instrument of knowledge and domain of nature. The art, in its turn, can mediate the elaboration of knowledge, whether it is scientific, technical, or philosophical. Science and art are products that express the imaginary representations from distinct cultures. The Brazilian Concretism, for its relations with the geometry, is the period in art history chosen as reference. Technology was represented by the computational environments, as a didactic support and an instrument for the accomplishment of practical activities. Microsoft Word is one of the basic softwares for this proposal because of its easy access in most public schools.
Keywords: Integration art/science/technology; Geometry teaching; Symmetry